(untitled) (International Journal of Environmental Sciences, 2025)
The biosynthesized ZnONPs demonstrated potent antibacterial activity against both Staphylococcus spp. (Gram-positive) and Pseudomonas spp. (Gram-negative), with inhibition zones increasing in a concentration-dependent manner. The highest inhibition zone for Staphylococcus was 25 ± 1.07 mm, while Pseudomonas exhibited a larger zone of 35 ± 1.19 mm, reflecting greater susceptibility (P < 0.001). These findings indicate that ZnONPs possess broad-spectrum antibacterial activity, with particularly strong effects on Gram-negative bacteria In terms of antiparasitic activity, both the fungal filtrate and ZnONPs showed time- and concentration-dependent effects against Echinococcus granulosus protoscoleces. At 4 hours, the crude filtrate achieved a maximum mortality rate of 94.1 ± 12.5%, while ZnONPs at 0.16 ppm reached 83.3 ± 5.14% (P < 0.01). After 24 hours, the efficacy of the crude filtrate declined sharply to approximately 20–23%, whereas ZnONPs at 0.08 ppm maintained moderate activity with a 33.3 ± 4.17% mortality rate. Interestingly, no activity was observed at 0.12 ppm, suggesting a non-linear dose response. By 48 hours, the crude filtrate had lost nearly all efficacy, and only the 0.08 ppm ZnONPs showed residual antiparasitic activity (25 ± 1.03%), while higher concentrations exhibited no significant effect. These results suggest that nanoparticle efficacy may be influenced by aggregation, saturation, or changes in bioavailability over time. Collectively, the study affirms the utility of P. ostreatus-derived ZnONPs as promising agents for antimicrobial and antiparasitic applications, with further optimization warranted for long-term effectiveness.